2021
DOI: 10.1186/s12903-021-01542-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing an eruption of teeth associated with a dentigerous cyst: a systematic review and meta-analysis

Abstract: Background A dentigerous cyst (DC) is a pathology embracing the crown of an unerupted tooth at risk of malignant transformation. The causal tooth is usually removed together with the cyst. However, if there are orthodontic contraindications for extraction, two questions arise. (1) Which factors favor spontaneous eruption? (2) Which factors imply the necessity of applying orthodontic traction? This systematic review aimed to identify factors conducive/inconducive to the spontaneous eruption of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
0
33
0
2
Order By: Relevance
“…The center of the cyst may be located above or below the crown, except when the tooth is not in an upright position or when the cyst orients laterally during its development. Other radiological signs, less specific to DC, are the boundaries of the lesion: generally, well-defined, rounded, a thin sclerotic margin [ 4 , 8 , 11 ], and the radiolucent homogeneous, unilocular internal appearance of the lesion [ 4 , 5 , 6 , 7 , 8 , 9 ]. On the other hand, the effects on the surrounding anatomical structures (adjacent teeth, bone cortex, IAC, nasal cavity, and maxillary sinus floor) can be variable and include discharge, displacement, and expansion or resorption [ 8 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The center of the cyst may be located above or below the crown, except when the tooth is not in an upright position or when the cyst orients laterally during its development. Other radiological signs, less specific to DC, are the boundaries of the lesion: generally, well-defined, rounded, a thin sclerotic margin [ 4 , 8 , 11 ], and the radiolucent homogeneous, unilocular internal appearance of the lesion [ 4 , 5 , 6 , 7 , 8 , 9 ]. On the other hand, the effects on the surrounding anatomical structures (adjacent teeth, bone cortex, IAC, nasal cavity, and maxillary sinus floor) can be variable and include discharge, displacement, and expansion or resorption [ 8 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A dentigerous cyst (DC), also known as a follicular cyst, is a cyst of non-inflammatory odontogenic origin that develops from the pericoronal tissue (dental sac or dental follicle) of an impacted tooth, either permanent or deciduous or supernumerary [ 1 , 2 , 3 , 4 , 5 , 6 ]. Several factors have been investigated and are known to play an important role in tooth eruption [ 7 ]. DCs represent more than 24% of the cysts of the maxilla [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies that evaluated the indicators for a spontaneous eruption and a cyst-associated tooth were systematically reviewed by Nahajowski et al [ 10 ] who concluded that the most critical factors are the patient's age younger than 10 years, less than half root formation. Other factors are tooth depth, inclination, and appropriate space [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in the PTHR1 gene have been associated with primary eruption failure (arrest of supraosseous eruption), and mutations in GNAS with other dental eruption defects [ 6 , 7 ]. Other factors, such as dentigerous cysts, and craniofacial deformities, such as cleft palate, have been described in association with abnormalities in dental eruption [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%